Characterisation of welded plate through micro-magnetic technique - Gupta S.K.; Mahto M.K.; Raja A.R.; Vashista M.; Yusufzai M.Z.K. (My University, 2025)
Characterisation of the welded plate by Non-destructive testing technique are gaining more popularity over destructive testing. In this study, the variation in the hysteresis loop behaviour were examined with the variation of magnetic field intensity on the base metal, heat affected zone and weld metal regions of gas metal arc welded ferritic stainless steel plate. The behaviour of hysteresis loop characteristics such as average permeability, remanence and coercivity have been investigated and it was found that these characteristics depend upon the grain size and microhardness as well as magnetic field intensity. Coercivity of each region vary in proportion with the variation of magnetic field intensity and inversely proportional to the grain size, but the variation of other hysteresis loop characteristics with the magnetic field intensity in each region is irregular. © 2019 Elsevier Ltd. All rights reserved.